Prevalence of Malocclusion in Adolescence (12-17 Years) in Najaf area. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: The aim of present study is to detect the prevalence of malocclusion in specific group aged between 12-17 years school children in Al-Najaf city of Iraq.Patient and methods: Cross sectional study composed of two groups that classified according to the gender into male and female groups, the study was done in randomly selected secondary school for male and others for female in Al-Najaf city, in the period between October, 2015 and May, 2016. Ten schools were randomly selected 788 females and 584 males were clinicaly examined aged between 12-17 years old.Results: The result shows Class I malocclusion was 88.04% according to Angle’s classification, whereas 8.03% show Class II Div.1, 1.31 % exhibit Class II Div. 2 and Class III malocclusion were present in 2.3%. Crowding was present in about 57%, While Excessive overjet, Negative overjet, anterior crossbites, Posterior crossbites show 16.1%, 3.4%, 10.34%, 12.68% respectively, Deep overbite were in 6.4%,  Open bite in 2.9%, Median diastema were in 2.7%.Conclusion:  Angle’s Class I malocclusion show maximum prevalence, followed by Angle’s Class II/1 and Class III, while Angle’s Class II/2 malocclusion shows the lowest percent of prevalence in secondary school of Al-Najaf.